The The Influence of Digital Advertising and Food Quality on Purchase Decision Through Purchase Intention on The Chicken Pecak XYZ in Medan City - Nanda Adilfa Mulya; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Indonesian Journal Publisher, 2026)
This research aims to analyze and determine the influence of Digital Advertising and Food Quality on Purchase Decisions for Pecak XYZ Chicken in Medan City with Purchase Interest as an intervening variable. The population in this study were customers of the Ayam Pecak XYZ Gatot Subroto outlet, Medan City. The sample used in this study was 126 people. The data collection technique in this research uses statement techniques or questionnaires. The data analysis technique uses descriptive analysis and PLS Structural Equation Model path analysis. Data processing in the research used Smart-PLS version 4. Based on the research results, it was found that Digital Advertising had no significant influence on Purchase Decisions, Food Quality had a positive and significant influence on Purchase Decisions, Digital Advertising had a positive and significant effect on Purchase Interest, Food Quality had a positive and significant influence on Purchase Interest, Purchase Interest had a positive and significant influence on Purchase Decisions, Purchase Interest significantly mediates the influence of Digital Advertising on Purchase Decisions, Purchase Interest significantly mediates the influence of Food Quality on Purchase Decisions. Based on the coefficient of determination, the percentage of Purchase Interest can be explained by Digital Advertising and Food Quality of 46.7%, while Purchase Decisions can be explained by Digital Advertising, Food Quality and Purchase Interest of 59.9%.